2020
DOI: 10.1039/c9dt03573g
|View full text |Cite
|
Sign up to set email alerts
|

A new synthesis of porphyrins via a putative trans-manganese(iv)-dihydroxide intermediate

Abstract: An efficient, milder (occurs at RT), scalable, and environmentally benign methodology for the facile synthesis of porphyrin derivatives without using quinone based oxidants has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 76 publications
1
11
0
Order By: Relevance
“…The main problem in porphyrin synthesis is its low yields (6%–20%) although different trials to enhance the yields of porphyrins are reported [24–26]. Recently, Fadda et al [27,28] reported a new methodology, which yields 70%–80% yield.…”
Section: Resultsmentioning
confidence: 99%
“…The main problem in porphyrin synthesis is its low yields (6%–20%) although different trials to enhance the yields of porphyrins are reported [24–26]. Recently, Fadda et al [27,28] reported a new methodology, which yields 70%–80% yield.…”
Section: Resultsmentioning
confidence: 99%
“…Kar and co-workers [ 133 , 134 ] have recently devel­oped a new simple two-step method for the synthesis of symmetrical and unsymmetrical meso -arylpor­phyrins. The first step is the condensation of pyrrole or dipyrromethane with an aldehyde in aqueous methanol in the presence of HCl (Scheme 5 ).…”
Section: Principal Methodologies Of the Synthesis Of Tetrapyrrole Mac...mentioning
confidence: 99%
“…1 H NMR (400 MHz, chloroform- d ) δ 8.85 (s, 8H), 8.25–8.19 (m, 8H), 7.79–7.72 (m, 12H), −2.78 (s, 2H) (Figure S1). Other analytical data are consistent with those of the previously reported authentic compounds …”
Section: Methodsmentioning
confidence: 99%
“…1 H NMR (400 MHz, chloroform- d ) δ 8.86 (s, 8H), 8.13 (d, J = 8.0 Hz, 8H), 7.29 (d, J = 8.0 Hz, 8H), 4.10 (s, 12H), −2.75 (s, 2H) (Figure S2). Other analytical data are consistent with those of the previously reported authentic compounds …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation